2016
DOI: 10.3390/jfb7020008
|View full text |Cite
|
Sign up to set email alerts
|

Glass Polyalkenoate Cements Designed for Cranioplasty Applications: An Evaluation of Their Physical and Mechanical Properties

Abstract: Glass polyalkenoate cements (GPCs) have potential for skeletal cementation. Unfortunately, commercial GPCs all contain, and subsequently release, aluminum ions, which have been implicated in degenerative brain disease. The purpose of this research was to create a series of aluminum-free GPCs constructed from silicate (SiO2), calcium (CaO), zinc (ZnO) and sodium (Na2O)-containing glasses mixed with poly-acrylic acid (PAA) and to evaluate the potential of these cements for cranioplasty applications. Three glasse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 41 publications
(54 reference statements)
0
12
0
Order By: Relevance
“…The network connectivity for KT1, KT2 and KT3 was calculated to be 2, 2.2 and 2.4, respectively [ 24 ], as increasing the amount of GeO increased network connectivity. XRD confirmed that no crystalline phases were present within the glasses ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The network connectivity for KT1, KT2 and KT3 was calculated to be 2, 2.2 and 2.4, respectively [ 24 ], as increasing the amount of GeO increased network connectivity. XRD confirmed that no crystalline phases were present within the glasses ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, in addition to maturation, strengths also increased with Ge content. Ge is a 4+ valency ion; thus, it will bond and increase the network connectivity (NC) of the cement [ 24 ]. Hill et al [ 38 ] described the entanglement of polyanion chains during GPC setting and how they limit lateral movement, while interactions with neighboring chains limit longitudinal movement.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations